Discord as Learning Platform: A Review of Liteature - Isnaini Hijriyah Kurniasari (Universitas Khairun, 2024)
The aim of this study to review the teachers and students perception toward Discord as tools in online learning especially during and after Covid-19 Pandemic. Total of 14 articles published since 2020 were reviewed. 3 articles reviewed about teacher perception and 11 articles reviewed about studentsâ€™ perceptions. Both teachers and students find Discord as challenging tools in online classroom although there are some students having problem with the internet connection due to rural area. Discord easy to operate even for students who are new to this application.Â